High-Intensity Intermittent Training Positively Affects Aerobic and Anaerobic Performance in Judo Athletes Independently of Exercise Mode - Franchini, Emerson; Julio, Ursula F.; Panissa, Valéria L. G.; Lira, Fábio S.; Gerosa-Neto, José; Branco, Braulio H. M. (Frontiers in Physiology, 2016)
PRUPOSE: The present study investigated the effects of high-intensity intermittent training (HIIT) on lower- and upper-body graded exercise and high-intensity intermittent exercise (HIIE, four Wingate bouts) performance, and on physiological and muscle damage markers responses in judo athletes. METHODS: Thirty-five subjects were randomly allocated to a control group (n = 8) or to one of the following HIIT groups (n = 9 for each) and tested pre- and post- four weeks (2 training d•wk−1): (1) lower-body cycle-ergometer; (2) upper-body cycle-ergometer; (3) uchi-komi (judo technique entrance). All HIIT were constituted by two blocks of 10 sets of 20s of all out effort interspersed by 10s set intervals and 5-min between blocks. RESULTS: For the upper-body group there was an increase in maximal aerobic power in graded upper-body exercise test (12.3%). The lower-body group increased power at onset blood lactate in graded upper-body exercise test (22.1%). The uchi-komi group increased peak power in upper- (16.7%) and lower-body (8.5%), while the lower-body group increased lower-body mean power (14.2%) during the HIIE. There was a decrease in the delta blood lactate for the uchi-komi training group and in the third and fourth bouts for the upper-body training group. Training induced testosterone-cortisol ratio increased in the lower-body HIIE for the lower-body (14.9%) and uchi-komi (61.4%) training groups. CONCLUSION: Thus, short-duration low-volume HIIT added to regular judo training was able to increase upper-body aerobic power, lower- and upper-body HIIE performance.